2020
DOI: 10.31235/osf.io/bws84
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and primary care: A critical need for strengthening emergency preparedness across health systems

Abstract: The coronavirus disease (COVID-19) pandemic has disrupted every frontier of human lives. When it comes to emergency care for any health emergency for individuals, or primary care where people make their first contact with the health system in a country, this pandemic has shown the lack of preparedness on delivering medical care in both settings. An integrative yet holistic perspective is needed to strengthen emergency medicine and primary care across health systems, which may enable us to save more lives durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The reviewed literature also mentioned that special emphasis should be given to the psychosocial needs of healthcare providers, so that they can fulfil their professional responsibilities during this pandemic. 30 This present study also revealed that during the COVID-19 pandemic, the mobilization of HWs from different sources was important for each locality. CHSs' representatives were also members of the National Steering Board for COVID-19 prevention and control at the level of communes/wards; therefore, they could efficiently cooperate with related stakeholders, who were also under the same umbrella.…”
Section: Health Workforcesupporting
confidence: 65%
See 1 more Smart Citation
“…The reviewed literature also mentioned that special emphasis should be given to the psychosocial needs of healthcare providers, so that they can fulfil their professional responsibilities during this pandemic. 30 This present study also revealed that during the COVID-19 pandemic, the mobilization of HWs from different sources was important for each locality. CHSs' representatives were also members of the National Steering Board for COVID-19 prevention and control at the level of communes/wards; therefore, they could efficiently cooperate with related stakeholders, who were also under the same umbrella.…”
Section: Health Workforcesupporting
confidence: 65%
“…The reviewed literature also mentioned that special emphasis should be given to the psychosocial needs of healthcare providers, so that they can fulfil their professional responsibilities during this pandemic. 30…”
Section: Discussionmentioning
confidence: 99%
“…Primary care and community-based health facilities play a vital role in delivering preventive and therapeutic health services in South Asian countries [ 114 , 115 , 116 ]. However, the current capacity of such community-level facilities to deliver mental health services during this pandemic may not be adequate to address the continued burden of mental disorders among the communities they serve [ 35 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, digital mental health has emerged as a promising approach to improve access to mental health services using digital devices and internet-based technologies 100 and therapeutic health services in South Asian countries [102][103][104] . However, the current capacity of such community-level facilities to deliver mental health services during this pandemic may not be adequate to address the continued burden of mental disorders among the communities they serve 33,96 .…”
Section: Implications For Mental Health Policymaking and Practicementioning
confidence: 99%